‘A jumping, joyous urban jumble’: Jane Jacobs’s Death and Life of Great American Cities as a phenomenology of urban place - Seamon, David (My University, 2017)
In this forum report, I contend that Jane Jacobs’s Death and Life of Great American Cities can be interpreted as a phenomenology of the city and urban place (Jacobs, 1961/1993). I consider four aspects of the book as they relate to a phenomenological approach: (1) Jacobs’s mode of seeing and understanding as phenomenological method; (2) her claim that ‘citiness’ is a phenomenon in its own right and has the power to draw and hold people to particular urban places; (3) her portrait of urban experience and place as they are founded in environmental embodiment; and (4) her pointing toward a constellation of place relationships and processes that potentially strengthen or weaken urban robustness. I argue that much of Jacobs’s argument has parallels with the findings of space syntax research, including themes highlighted by Julienne Hanson in her 2000 article, ‘Urban Transformations’ (Hanson, 2000).
Citation: Seamon, D. (2012). ‘A jumping, joyous urban jumble’: Jane Jacobs’s Death and Life of Great American Cities as a phenomenology of urban place. The Journal of Space Syntax,3(1), 139-149. http://joss.bartlett.ucl.ac.uk/journal/index.php/joss/article/view/121
Keywords: Jane Jacobs; Julienne Hanson; Phenomenology of city; Place; Urban place; Place ballet